A PROPOSAL FOR A HYBRID POWER TRAIN FOR A TRUCK - Rossato, D. A. S.; Cornel, H. B.; Brites, L. G. A.; Diógenes, A. N. (Revista de Engenharia Térmica, 2023)
Aiming at reducing the emission of pollutants from automotive vehicles, international commissions indicate, at each given period, a target of admissible values for these pollutants, to be implemented by the automakers. A case like the future implementation of EuroVII, from 2025, in European regions. In parallel to these conditions, there are many studies with the objective of seeking alternatives for the propulsion of these combustion vehicles, for example, the application of fully electric or hybrid vehicles. This article aims to develop and implement a mathematical model for a proposal for a hybrid engine, in a low-power truck, resulting in a small diesel engine, powering the vehicle’s alternator and battery, generating the charging for use in a main electric motor, that is, to develop with a focus on energy conservation and the environment, with a reduction in the size of a combustion engine and its emissions.